Wonders never cease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The miracle tree. The multiple attributes of Moringa Edited by L J Fuglie, CWS CTA copublication, 2001. 172 pp. CTA number 1062. 20 credit points